Normal and Reverse Flow Injection- Spectrophotometric Determination of Vancomycin Hydrochloride in Pharmaceutical Preparations Using 2, 4-Dinitrophenylhydrazine - Yousef, Fadi; Al-Abachi, Mouyed (Iraqi Journal of Science, 2023)
Simple and sensitive batch and flow injection methods (normal and reverse flow injection analysis (nFIA and rFIA)) for spectrophotometric determination of vancomycin hydrochloride (VHC) in pharmaceutical preparations were proposed and optimized. Both methods are based on the oxidative - coupling reaction between vancomycin hydrochloride and 2,4-Dinitrophenylhydrazine (DNPH) in the presence of sodium periodate in alkaline medium to form a yellow water-soluble product that is stable and has a maximum absorption at 461 nm. Beer’s law was obeyed over the range of 1- 40, 0.5-120 and 0.5-150 μg.mL-1; the limits of detection were 0.537, 0.0823 and 0.233 μg.mL-1 for batch, normal and reverse flow injection methods respectively. The sampling rates were 124 and 120 injections per hour for normal and reverse flow injection methods respectively. The effects of chemical and physical parameters have been carefully considered and the proposed procedures were successfully applied to the determination of vancomycin hydrochloride in pharmaceutical preparations